From Acidic Water to Neutralization Process: Unravelling the Efficacy and Stability of Alkaline Agents for Acid Mine Drainage - Abfertiawan, Muhammad Sonny (Program Studi Teknik Pertambangan Universitas Trisakti, 2024)
Acid mine drainage (AMD) arises as a major environmental challenge in the mining industry, resulting from the reaction of sulphide minerals with oxygen and water to produce sulfuric acid. Evaluating and optimizing AMD neutralization methods is crucial for mitigating its environmental impact. This study assessed the effectiveness and stability of alkaline agents for neutralization, comparing caustic soda and hydrated lime in bench-scale laboratory experiments. Jar tests were performed by rapid mixing at 120 rpm for one minute, followed by slow mixing at 60 rpm for 20 minutes. The experiments showed increased AMD's pH after contact with neutralizing agents. The optimal doses were 815 mg/L for caustic soda, 1200 mg/L for hydrated lime, and 800 mg/L for a combination of 18%w/w hydrated lime and 82%w/w caustic soda. The stability of the neutralization process, evaluated using pH as an indicator, varied in the following order: hydrated lime, combination, and caustic soda. Hydrated lime demonstrated better stability than caustic soda. Interestingly, caustic soda caused a more rapid pH change when reintroducing AMD. This study provides insights into effective alkaline agents for the mining industry.